Utilization of Tea Waste Activated by Using Hydrochloric Acid as An Adsorbent for Calcium (II) Ions in Hard Water - Meizaristy Ananta Wuryani; Agus Taufiq; Muhammad Fathurrahman (Universitas Pakuan, 2023)
Water is an important natural resource for human survival. Groundwater in calcareous soil areas contains high levels of Ca(HCO3)2 and Mg(HCO3)2 salts and will have a negative impact if consumed continuously. In this study, an adsorption method using tea waste (Camellia sinensis) was conducted to reduce the concentration of Ca(II) ions that cause water hardness. Tea waste was activated with 0.1 N HCl for 24 hours. Tea waste was characterized by Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). Determination of optimum conditions was carried out at pH variations of 4, 6, and 8, with contact times of 30 minutes, 60 minutes and 90 minutes, and adsorbent weights were 0,5 grams, 1 gram, 1.5 grams and 2 grams. Tea waste with the best optimum conditions was tested on Ca(II) solutions of various concentrations from 30, 50, and 70 mg/L respectively to determine the maximum capacity for Ca(II) metal ions and the type of adsorption isotherm. Then applied to well water samples analyzed by Inductively Coupled Plasm (ICP) to determine the capacity of Ca(II) that can be absorbed by each adsorbent. The results showed that to utilize 0.1 N HCl-activated tea waste as an adsorbent for Ca(II) metal ions were optimum at pH 8, with a contact time of 30 minutes and an adsorbent weight of 0.5 grams. The maximum adsorption capacity was obtained at Ca(II) solution concentration of 70 mg/L with an adsorption capacity value of 6.704 mg/g. The adsorption isotherm corresponding to the tea waste adsorbent is the Freundlich isotherm (r2 = 0.9199). The highest absorption of Ca(II) metal ions in well water samples from the concentration of Ca(II) metal ions was 72.7702 mg/L to 4.877 mg/L, with adsorption efficiency of 93.3% and adsorption capacity of 6.7893 mg/g.